The effect of two doses of fentanyl on chest wall rigidity at equipotent doses of isoflurane in dogs. (May 2019) - Soares, João HN.; Henao-Guerrero, Natalia; Pavlisko, Noah D.; Williamson, Allan; Giannella-Neto, Antonio
Abstract: Objective: To evaluate the effect of two doses of fentanyl upon chest wall rigidity of dogs anesthetized at equipotent doses of isoflurane [1.3 minimum alveolar concentration (MACISO ) of each dose of fentanyl]. Study design: Prospective crossover randomized study. Animals: A group of eight male Beagle dogs, approximately 1 year old and weighing 12.1 ± 1.6 kg (mean ± standard deviation). Methods: The dogs were anesthetized with isoflurane and instrumented for the measurement of esophageal pressure (PESO ), flow ( V ˙ ) and volume ( V ). Chest wall elastance (ECW ) was estimated by multiple linear regression of the model. PESO (t) = V ˙ (t) × RCW  + V(t) × ECW  + EEPESO where t is time, RCW is chest wall resistance and EEPESO is end-expiratory PESO . Chest wall compliance (CCW ) was calculated as 1/ECW and normalized to the body weight of each dog (mL cmH2 O −1 kg −1 ). Anesthesia was maintained at 1.3 MACISO for at least 15 minutes and CCW recorded (CCW-ISO ). The dogs were randomly assigned to the lower fentanyl dose [loading dose (33 μg kg −1 ) and infusion (0.2 μg kg −1 minute −1 )] or the higher fentanyl dose [loading dose (102 μg kg −1 ) and infusion (0.8 μg kg −1 minute −1 )]. After 60 minutes of fentanyl infusion, CCW was recorded for each dose (CCW-FENT ). During fentanyl infusion, the dogs were maintained at equipotent doses of isoflurane (1.3 MACISO for each fentanyl dose). A two-way analysis of variance followed by a Bonferroni test was used to compare CCW-ISO and CCW-FENT in both treatments and CCW-FENT between treatments. A p value <0.05 was considered significant. Results: Neither of the fentanyl doses decreased CCW and there was no difference in CCW-FENT between doses. Conclusions and clinical relevance: Fentanyl at the studied doses did not result in chest wall rigidity in dogs anesthetized with equipotent doses of isoflurane (1.3 MACISO ).